2012
DOI: 10.4081/reumatismo.2012.286
|View full text |Cite
|
Sign up to set email alerts
|

Fibromyalgia and arthritides

Abstract: Fibromyalgia (FM) is a chronic pain syndrome that affects at least 2% of the adult population. It is characterised by widespread pain, fatigue, sleep alterations and distress, and emerging evidence suggests a central nervous system (CNS) malfunction that increases pain transmission and perception. FM is often associated with other diseases that act as confounding and aggravating factors, such as rheumatoid arthritis (RA), spondyloarthritides (SpA), osteoarthritis (OA) and thyroid disease. Mechanism-based FM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Peripherally based models clearly cannot explain much of the variance in pain, fatigue, sleep, memory problems and functional disability that is not accounted for by peripheral factors alone. For example, although the pathological focus in osteoarthritis (OA) is the joint and surrounding structures, patients with knee OA frequently experience multifocal pain in areas unaffected by OA (4,5). Similarly, there are other somatic symptoms that cannot be explained on the basis of a purely peripheral condition: studies have found that fatigue is a major problem in patients with knee OA as many of them find it a more functionally limiting symptom than pain (5,8).…”
Section: N the Role Of Centralised Pain In Classic Rheumatic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripherally based models clearly cannot explain much of the variance in pain, fatigue, sleep, memory problems and functional disability that is not accounted for by peripheral factors alone. For example, although the pathological focus in osteoarthritis (OA) is the joint and surrounding structures, patients with knee OA frequently experience multifocal pain in areas unaffected by OA (4,5). Similarly, there are other somatic symptoms that cannot be explained on the basis of a purely peripheral condition: studies have found that fatigue is a major problem in patients with knee OA as many of them find it a more functionally limiting symptom than pain (5,8).…”
Section: N the Role Of Centralised Pain In Classic Rheumatic Diseasesmentioning
confidence: 99%
“…For example, although the pathological focus in osteoarthritis (OA) is the joint and surrounding structures, patients with knee OA frequently experience multifocal pain in areas unaffected by OA (4,5). Similarly, there are other somatic symptoms that cannot be explained on the basis of a purely peripheral condition: studies have found that fatigue is a major problem in patients with knee OA as many of them find it a more functionally limiting symptom than pain (5,8). Peripherally based theories of the pathogenesis of OA, systemic lupsu erythematosus (SLE), and inflammatory arthritis simply do not explain why these other symptoms are so common and often refractory to standard therapies (1,5).…”
Section: N the Role Of Centralised Pain In Classic Rheumatic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with arthritis may experience recurrent acute pain mainly related to exercise related or almost continuous pain that is present even at rest, whereas unremitting pain is more a feature of chronic widespread pain (CWP); furthermore, some patients with RA and OA feel pain mainly at rest and they find that it improves with exercise [5,8]. Consequently, an all-encompassing description such as 'chronic' pain does not usually reflect individual experience accurately.…”
Section: Pain In Systemic Rheumatic Diseasesmentioning
confidence: 97%
“…Even when a patient has clear-cut evidence of the existence of an inflammatory joint disease, such as positive serological test and erosions on X-rays, this still does not mean that all pain is attributable to this diagnosis. In clinical practice, a high proportion of patients previously diagnosed as suffering from rheumatoid arthritis, ankylosing spondylitis, or systemic lupus erythematosus (SLE) will exhibit comorbid fibromyalgia at least to some extent [12]. This of course makes it highly imperative that the rheumatologist, being in charge of treating patients with pain in their joints, bones, and muscles, be highly acquainted with and feel very comfortable treating elements of centralized pain (e.g., fibromyalgia).…”
Section: Deconstructing the Pain Experiencementioning
confidence: 98%